The Effect of Self-Efficacy and Locus of Control on MSME Entrepreneurs’ Performance - Miftakul Huda; Titiek Ambarwati; Sandra Irawati (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine the effect of self-efficacy and locus of control on the performance of MSME entrepreneurs. This research was conducted on entrepreneurs who have been in business for more than 5 years with a sample of 100 respondents. The analysis technique used in this research is the multiple linear regression analysis technique. The results showed that the variables of self-efficacy, locus of control, and entrepreneur performance were high, judging from the range of the scales, the scores were very high. The results of the regression analysis of self-efficacy and locus of control each have a partial and simultaneous effect on the performance of entrepreneurs, the self-efficacy variable is the variable that has the most influence on the performance of entrepreneurs in SMEs in the Gandusari district.